A SiO X / Microcrystalline graphite negative electrode material and its preparation method and application

By filling nano SiO2 particles in the surface and grain gap of microcrystalline graphite and forming a core-shell structure of carbon clad layer, the cracking and powdering problems caused by volume expansion of lithium-ion battery negative electrode materials during charging and discharging are solved, and the cracking and powdering problems caused by volume expansion during charging and discharging are improved. The energy density and cycle stability of the battery are achieved.

CN119263286BActive Publication Date: 2025-02-25SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD

Patent Information

Application Number
CN202411797296.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-25
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The volume expansion rate of existing lithium-ion battery anode materials due to silicon lithium alloying during charging and discharging is high, which can easily lead to cracking, powdering and frequent destruction and reconstruction of irreversible electrolyte membranes, thereby reducing the energy density and life of the battery.

Method used

Using the SiOX/microcrystalline graphite negative electrode material grown in situ, nano SiO2 particles are filled in the surface and grain gap of the microcrystalline graphite through hydrolysis and hydrothermal reaction, and a core-shell structure with a carbon coating is formed by carbonization. .

Benefits of technology

It effectively suppresses the volume expansion of silicon particles during charging and discharging, improves the energy density and cycling stability of the material, and reduces the expansion rate of the electrode sheet and the failure frequency of the SEI film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263286B_ABST
    Figure CN119263286B_ABST
Patent Text Reader

Abstract

The invention discloses a SiO X / Microcrystalline graphite negative electrode material and its preparation method and application; relates to the technical field of lithium battery negative electrode materials. The preparation method comprises using microcrystalline graphite as a matrix material, using a hydrothermal reaction method to in-situ grow nano silicon oxide particles on the surface of microcrystalline graphite and in the gaps between the sheets to form SiO X / microcrystalline graphite composites, and in the SiO X The surface of the microcrystalline graphite composite material is coated with a carbon coating layer with a complete carbon layer structure, and finally a SiO X / Microcrystalline graphite negative electrode material. The technical solution of the present invention uses the structure of microcrystalline graphite flakes with different structural orientations to offset and suppress the stress caused by silicon volume expansion during the charging and discharging process; at the same time, nano-SiO X The particles are filled in the gaps of the microcrystalline graphite flake layers, and the fine flake graphite builds a three-dimensional conductive network structure, improving the SiO X The problem of poor electrical conductivity of particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery negative electrode materials, and in particular to a SiO X / Microcrystalline graphite negative electrode material and its preparation method and application. Background Art

[0002] Natural graphite includes crystalline graphite and microcrystalline graphite. Crystalline graphite is flaky, and the scales are large, and the aggregates are well oriented. The particle size of crystalline graphite is generally between 25 and 100 μm. In particular, the particle size of large flake graphite can reach 1 to 5 mm. However, the crystal diameter of microcrystalline graphite is usually less than 1 μm, and it is in the form of a microcrystalline aggregate. Its grains are small, and the particle layer structure has different orientations to form a chaotic layer structure. However, compared with crystalline graphite, it has a lower price, and the chaotic layer structure with different orientations gives it better rate performance, so it can be used as a negative electrode material for lithium batteries; using it as a matrix material will greatly reduce the cost of negative electrode materials, and can provide new application directions for the development and utilization of microcrystalline graphite.

[0003] As an energy storage device, lithium-ion batteries are widely used in various fields, such as electronic products, energy storage base stations, electric vehicles, etc., and are currently the most widely used energy storage devices. However, with the development of society and the continuous innovation of science and technology, the energy storage performance of lithium-ion batteries is required to be higher and higher, and lithium-ion batteries are urgently expected to have higher energy density and longer life. The theoretical specific capacity of silicon is 4200 , far exceeding traditional graphite (372 ) negative electrode material is more than ten times, so using silicon as the negative electrode material can greatly improve the energy density of lithium-ion batteries. In addition, the charging platform of silicon is slightly higher than that of graphite, the possibility of lithium precipitation is smaller, and the safety is better than that of graphite. More importantly, silicon is one of the most abundant elements in the earth's crust, with a wide source and low price. Therefore, silicon negative electrode materials have broad application prospects in the field of lithium-ion power batteries. However, the volume expansion rate of silicon negative electrode caused by silicon-lithium alloying during charging is as high as 400%, which can easily lead to cracking and pulverization of silicon negative electrode, and rapidly increase the internal resistance of the battery. In addition, the continuous volume expansion and contraction of silicon negative electrode leads to the destruction of structure during charging and discharging, causing the active material to fall off from the current collector, and continuously forming irreversible electrolyte film, causing frequent destruction and reconstruction of solid electrolyte interface film (SEI film), consuming a large amount of lithium ions and electrolytes, and rapidly decaying battery capacity, which ultimately leads to the problems of low reversible capacity, poor cycle stability and rate performance of silicon negative electrode materials.

[0004] The prior art usually uses graphite as the matrix material, and reduces the volume change of the negative electrode material by loading silicon-based materials, and at the same time solves the problem of poor conductivity of silicon-based materials. However, due to the weak interface bonding force between graphite and silicon, the volume expansion of silicon particles on the graphite surface along the direction of graphite sheets is difficult to control. Therefore, although the silicon-carbon composite material structure has a slight improvement on the cycle performance, it is relatively limited. Therefore, the prior art forms porous carbon by forming pores in graphite, and deposits silicon particles in the pores. The porous structure provides space for silicon-based expansion, thereby avoiding the cracking and differentiation of the silicon negative electrode caused by the volume expansion of silicon. However, compared with porous carbon, microcrystalline graphite has different pore structure characteristics. Porous carbon has micropores, mesopores and macropores. Conventional silicon deposition methods can directly deposit silicon oxide particles in macropore structures, while the gaps between microcrystalline graphite crystallites generally result in the inability to directly apply silicon deposition methods for porous carbon to the pores of microcrystalline graphite. On the other hand, the natural pore structure of microcrystalline graphite eliminates the need to create pores in carbon-based materials, thereby reducing operational procedures and lowering production costs.

[0005] In order to solve the above problems, the present invention provides an in-situ grown SiO X / A method for preparing a microcrystalline graphite negative electrode material, wherein microcrystalline graphite is selected as a matrix material for silicon filling to increase the specific capacity of the negative electrode material. Summary of the invention

[0006] The present invention provides a SiO X / Microcrystalline graphite negative electrode material and its preparation method and application, so that the prepared microcrystalline graphite negative electrode material has the advantage of high specific volume.

[0007] In order to achieve the above object, the present invention provides a SiO X / A method for preparing a microcrystalline graphite negative electrode material, comprising using microcrystalline graphite as a matrix material, firstly, hydrolyzing SiO 2 Particles and / or silica gel are in-situ grown on the surface of microcrystalline graphite and filled in the gaps between the grains; a secondary filling is then performed through a hydrothermal reaction to obtain SiO X / microcrystalline graphite composite material precursor; then, the SiO X The precursor of the microcrystalline graphite composite material is dried and calcined at high temperature to obtain SiO X / microcrystalline graphite composite material; Finally, the SiO X The SiO2 / microcrystalline graphite composite material is uniformly mixed with the carbon source material and then carbonized. X The surface of the composite material is coated with carbon, forming a core-shell structure of SiO X / Microcrystalline graphite negative electrode material.

[0008] Preferably, the hydrolysis reaction comprises: heating in a water bath under ultrasonic conditions, so that the product of the hydrolysis reaction grows in situ on the surface of the microcrystalline graphite and fills the gaps in the microcrystalline graphite.

[0009] Preferably, the hydrothermal reaction comprises: the excess silicon source continues to react to produce a white precipitate, which is deposited in the gaps of the microcrystalline graphite for secondary filling to obtain the SiO X / microcrystalline graphite composite material precursor. The present invention uses nano-SiO 2 The pores of the microcrystalline graphite are completely filled by filling the surface of the microcrystalline graphite and the gaps between the grains through a hydrolysis reaction, and then a secondary filling is performed through a hydrothermal reaction. Furthermore, the volume expansion of the silicon particles is suppressed by the structural characteristics of the microcrystalline graphite, such as the gaps between the grains and the different orientations of the lamellar structure.

[0010] Preferably, the water bath heating includes a first water bath heating and a second water bath heating.

[0011] Specifically, the first water bath heating includes: dispersing microcrystalline graphite in a silicon source solution, stirring evenly and adjusting the pH, heating under ultrasonic conditions to perform a hydrolysis condensation reaction, and the generated white precipitate nucleates in situ on the surface of the microcrystalline graphite and in the gaps between the grains.

[0012] More preferably, the temperature of the first water bath heating is 40-60° C. and the reaction time is 1-3 h.

[0013] More preferably, after the first water bath heating is completed, the silicon source solution is continuously added dropwise until no white precipitate is generated.

[0014] Specifically, the second water bath heating includes: continuing the hydrolysis condensation reaction, and white precipitates are deposited on the surface of the microcrystalline graphite and in the gaps between the grains.

[0015] More preferably, the second water bath heating condition includes 60-80° C., heating for 0.5-1 h;

[0016] As one of the most preferred modes, in the reactions of the first water bath heating and the second water bath heating, the silicon source is kept in excess.

[0017] As one of the most preferred embodiments, the temperature of the second water bath heating is higher than the temperature of the first water bath heating.

[0018] In some specific embodiments, the temperature difference between the first water bath heating and the second water bath heating is 20-35°C.

[0019] As a preferred embodiment, the SiO X / The preparation method of microcrystalline graphite negative electrode material comprises the following steps:

[0020] S1. Hydrolysis reaction: disperse the microcrystalline graphite in the silicon source solution, stir evenly, adjust the pH, and perform a first water bath heating under ultrasonic conditions until there is no increase in white precipitate; then perform a second water bath heating to obtain a reaction mixture;

[0021] S2. Hydrothermal reaction: Add the reaction mixture into a reactor and perform a hydrothermal reaction to obtain SiO X / microcrystalline graphite precursor;

[0022] S3. Drying and calcining: After the precursor is dried, it is calcined at high temperature in an inert gas atmosphere to obtain SiO X / microcrystalline graphite composites;

[0023] S4. Coating carbonization: In the SiO X A carbon source precursor is added to the microcrystalline graphite composite material, mixed evenly, and then carbonized in an inert gas atmosphere to form a carbon coating layer to obtain a negative electrode material precursor;

[0024] S5. Pore sealing: introducing an organic carbon source into the negative electrode material precursor, and sealing the pores in the carbon coating layer by chemical vapor deposition, so that the carbon coating layer has a complete carbon layer structure; thus, SiO X / Microcrystalline graphite negative electrode material.

[0025] In any of the above technical solutions, in S1, the first water bath heating includes a hydrolysis reaction of the silicon source and water under the action of ammonia water.

[0026] Preferably, the reaction time is 1 to 3 hours.

[0027] Preferably, the pH is 9-12.

[0028] Preferably, the ultrasonic condition includes a frequency of 20-40 kHz.

[0029] Specifically, in the silicon source solution, the silicon source is ethyl orthosilicate, and the solvent of the silicon source solution is ethanol.

[0030] Preferably, the volume ratio of the silicon source to ethanol is 2:(5-10).

[0031] Preferably, the volume ratio of the silicon source to water is 1:(1-2).

[0032] Preferably, based on 1 g of microcrystalline graphite, the added amount of the silicon source is 5-15 mL / g.

[0033] Preferably, the mass percentage of aqueous ammonia is 25%.

[0034] Wherein, in the silicon source solution, the mass percentage of silicon source is greater than 99%, and the mass percentage of ethanol is greater than or equal to 99.7%.

[0035] In any of the above technical solutions, in S2, the temperature of the hydrothermal reaction is 180-220° C., and the reaction time is 2-10 hours.

[0036] In any of the above technical solutions, in S3, the drying temperature is 100-120° C., and the drying time is 5-8 hours.

[0037] Preferably, the high temperature calcination conditions include a calcination temperature of 800-1000° C. and a calcination time of 1-3 hours.

[0038] In any of the above technical solutions, in S4, the carbon source precursor includes soft carbon or hard carbon.

[0039] Preferably, the carbonization temperature is 1100-1400°C.

[0040] Preferably, in S3 and S4, the inert gas is nitrogen or argon;

[0041] In any of the above technical solutions, in S5, the organic carbon source includes a combination of one or more of methane, ethane, propane, acetylene, ethylene, propylene, and toluene.

[0042] The organic carbon source and SiO X / microcrystalline stone composite material ratio is 0.04~0.2.

[0043] The chemical vapor deposition conditions include: feeding the negative electrode material precursor into a fluidized bed reactor, the reaction pressure is 0.2-0.3 MPa, and the reaction temperature is 700-800°C.

[0044] In any of the above technical solutions, the microcrystalline graphite is microcrystalline graphite particles obtained by crushing, flotation, pulverizing, grading and purifying the microcrystalline graphite ore.

[0045] Preferably, the carbon content of the microcrystalline graphite particles is ≥99.5%, D 50 =8~18μm, tap density is 0.5~1g / cc, specific surface area is 5-15m 2 / g.

[0046] As one of the purposes of the invention, the present invention also provides a SiO X / microcrystalline graphite negative electrode material, prepared by the above-mentioned preparation method; the SiO X / Microcrystalline graphite negative electrode material has a core-shell structure; the core is SiO X / microcrystalline graphite composite material, nano silicon oxide particles are filled in the gaps between the microcrystalline graphite sheets; the outer shell is a carbon coating layer with a complete carbon layer structure; the carbon coating layer is wrapped around the SiO X / Surface of microcrystalline graphite composite material.

[0047] Preferably, the SiO X / The mass percentage of the core in the microcrystalline graphite negative electrode material is 92~97%; SiO X The mass percentage of silicon filled in the microcrystalline graphite composite material is 10~25%.

[0048] As one of the purposes of the invention, the present invention also provides a lithium ion battery, comprising at least the aforementioned SiO X / Microcrystalline graphite composite negative electrode material.

[0049] Beneficial technical effects obtained by the present invention:

[0050] 1. The nano-SiO provided by the present invention X The negative electrode material filled with microcrystalline graphite has a core-shell structure, with the core being SiO X / microcrystalline graphite composites, nano-SiO X The particles are deposited on the surface of the microcrystalline graphite layer and in the gaps between the grains. The outer shell is a carbon coating with a complete carbon layer structure and is wrapped in SiO X On the one hand, the present invention uses microcrystalline graphite as the matrix material, and utilizes the characteristics of the stratified structure of microcrystalline graphite with different orientations. X Filling the gaps in the grains can offset and suppress the stress caused by the volume expansion of silicon during the charge and discharge process; on the other hand, nano-SiO X The particles are filled in the gaps of microcrystalline graphite flakes, which are also SiO X The particles provide a three-dimensional conductive network structure, solving the problem of SiO X The problem of poor conductivity of particles; at the same time, nano-SiO X Filling particles in the gaps of microcrystalline graphite can also increase the energy density, true density and tap density of the material, thereby solving the defect of low specific capacity of graphite.

[0051] 2. The present invention adopts a method combining hydrothermal reaction and ultrasonic exfoliation to disperse the microcrystalline graphite while performing a hydrolysis-condensation reaction. On the one hand, it can promote the full contact between the reaction solution and the microcrystalline graphite grains, and at the same time improve the dispersibility of the graphite particles, so that the precipitate can be fully deposited in the gaps, thereby satisfying the deposition of silica particles; further, the hydrothermal reaction can continue to hydrolyze the obtained nano-silica particle precursor, so that the silica gel can be further deposited in the gaps of the grains to complete the secondary filling.

[0052] 3. Using the technical solution of the present invention to make nano-SiO X There is a certain amount of free space in the gaps between the grains of microcrystalline graphite, so that the negative electrode material has a volume self-absorption effect on the expansion of silicon during the charge and discharge process, which greatly reduces the expansion effect of silicon, thereby reducing the pole piece expansion rate during the charge and discharge process, ensuring good electrical contact between active substances, and reducing the rupture and repair of the SEI film due to pole piece expansion. Therefore, the graphite-based silicon-carbon composite negative electrode material provided by the present invention has excellent cycle performance.

[0053] 4. The technical solution of the present invention is different from the hole structure of porous carbon in the prior art. The structure belongs to the natural structure. It depends on the characteristics of the chaotic layer structure of microcrystalline graphite. No additional treatment is required to achieve nano-SiO X In-situ filling, especially in the recycling of negative electrode materials, can be SiO X The repeated expansion action provides free space, and there will be no problem of silicon particles falling off and causing attenuation of the negative electrode material.

[0054] 5. The nano-SiO provided by the present invention X The microcrystalline graphite negative electrode material is different from the traditional silicon-graphite negative electrode material. X The distribution of particles is neither on the surface of graphite particles nor in the pore structure of graphite materials, but is filled in the gaps between the grains of microcrystalline graphite, so there is no need to make pores or modify the surface of graphite; X The outer carbon coating layer of the microcrystalline graphite composite material can further stabilize the structure of the internal composite material, so that the microcrystalline graphite negative electrode material forms a stable overall structure, thereby further improving the first coulomb efficiency and cycle performance of the negative electrode material, and the carbon coating layer can also improve the SiO X / The specific surface area of ​​the microcrystalline graphite composite material inhibits the occurrence of side reactions when it is used as a negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is a cross-sectional SEM image of the microcrystalline graphite grains used in Example 1 of the present invention.

[0056] Figure 2 The SiO prepared in Example 1 of the present invention X / Cross-sectional SEM image of microcrystalline graphite negative electrode material.

[0057] Figure 3 The SiO prepared in Example 1 of the present invention X / The first charge and discharge curve of microcrystalline graphite negative electrode material.

[0058] Figure 4 The SiO prepared in Example 1 of the present invention X / Capacity and capacity retention rate curve of microcrystalline graphite negative electrode material after 500 cycles. DETAILED DESCRIPTION

[0059] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0060] The present invention provides a SiO X / A method for preparing a microcrystalline graphite negative electrode material, comprising using microcrystalline graphite as a base material, using a hydrolysis reaction to in-situ grow silica gel on the surface of the microcrystalline graphite, and filling the gaps between the grains, and then performing a secondary filling by a hydrothermal reaction to obtain SiO X / microcrystalline graphite composite material precursor; then, the SiO X The precursor of the microcrystalline graphite composite material is dried and then calcined at high temperature to obtain SiO X / microcrystalline graphite composite material; Finally, the SiO X The SiO2 / microcrystalline graphite composite material is mixed with the carbon source material, carbonized and sealed. X The surface of the composite material of microcrystalline graphite forms a carbon coating with a complete carbon layer structure, and finally obtains a SiO X / Microcrystalline graphite negative electrode material.

[0061] The present invention combines a hydrolysis reaction with a hydrothermal reaction, firstly performs in-situ nucleation on the surface of microcrystalline graphite and the gap between grains through a primary hydrolysis reaction, and then accelerates the nucleation speed through a secondary hydrolysis reaction to deposit silica gel; the purpose of this step is to enable the silica gel to achieve in-situ nucleation in the gap between grains of the microcrystalline graphite, and then achieve silicon oxide filling; further, the gap between grains is filled for a secondary time while continuing to react through the hydrothermal reaction to compensate for the incomplete filling of the hydrolysis reaction.

[0062] Furthermore, the carbon coating layer will produce pores of 3 to 20 nm during the carbonization process, resulting in an increase in the specific surface area of ​​the negative electrode material, thereby affecting its first coulombic efficiency and cycle stability as a negative electrode material. Therefore, the present invention seals the nanopores of the carbon coating layer through chemical vapor deposition to obtain a carbon coating layer with a complete carbon layer structure, thereby reducing the specific surface area of ​​the negative electrode material, thereby improving its energy density, first coulombic efficiency and cycle performance, and reducing the loss of volumetric efficiency.

[0063] Preferably, the hydrothermal reaction comprises: performing a water bath heating reaction under ultrasonic conditions to hydrolyze ethyl orthosilicate to generate some silicon dioxide nanoparticles and silanols in the gaps of microcrystalline graphite, and further filling the gaps of microcrystalline graphite with silica gel through a hydrothermal reaction to obtain the SiO X / microcrystalline graphite composite material precursor.

[0064] Preferably, the water bath heating reaction includes a first water bath heating and a second water bath heating.

[0065] More preferably, the first water bath heating comprises dispersing microcrystalline graphite in a silicon source solution, stirring evenly and adjusting the pH, and heating under ultrasonic conditions to form a white precipitate, namely, silicic acid gel.

[0066] More preferably, during the second water bath heating process, the white precipitate is deposited on the surface of the microcrystalline graphite and in the gaps between the sheets.

[0067] In the present invention, silicon is deposited on the surface of microcrystalline graphite and between grains in the form of silicon oxide through two water bath heating reactions. The first water bath heating reaction is the in-situ nucleation of silicon dioxide, and the purpose of the second water bath heating is to accelerate the nucleation rate, so that silicon dioxide nucleates quickly and has a small particle size and is deposited between the microcrystalline graphite grains.

[0068] More specifically, the SiO X / The preparation method of microcrystalline graphite negative electrode material comprises the following steps:

[0069] S1. In situ growth: disperse microcrystalline graphite in a mixed solution of silicon source solution and water, stir evenly and adjust the pH, perform water bath heating for the first time under ultrasonic conditions until there is no increase in white precipitate; then, perform water bath heating for the second time to obtain a mixed solution;

[0070] S2. Hydrothermal reaction: Add the mixed solution into a reactor and perform a hydrothermal reaction to obtain SiO X / microcrystalline graphite precursor; the purpose of this step is to perform secondary filling, further allowing the excess silicon source in the hydrolysis reaction to react to generate silica gel, and fill it on the surface of the microcrystalline graphite and in the gaps between the grains, and then undergo hydrolysis reaction and hydrothermal reaction in sequence to obtain a composite material precursor in a gel state;

[0071] S3. Drying and calcining: The SiO X After the microcrystalline graphite precursor is dried, it is calcined at high temperature in an inert gas atmosphere to obtain SiO X / microcrystalline graphite composite material; the SiO X / The precursor of microcrystalline graphite is silica gel. During the calcination process, the precursor in gel form generates silicon dioxide particles. Further, silicon dioxide undergoes a disproportionate reaction to generate silicon oxide, which is finally attached to the surface of microcrystalline graphite in the form of silicon oxide and filled in the gaps between the grains of microcrystalline graphite. At this point, the filling process of microcrystalline graphite is completed, and SiO X / microcrystalline graphite composites;

[0072] S4. Coating carbonization: In the SiO X A carbon source precursor is added to the microcrystalline graphite composite material, mixed evenly, and carbonized under an inert gas atmosphere to obtain SiO X / microcrystalline graphite negative electrode material; the carbonized carbon source precursor is wrapped in SiO X / microcrystalline graphite composite material surface, forming a carbon coating layer to obtain a negative electrode material precursor;

[0073] S5. Pore sealing: introducing an organic carbon source into the precursor of the negative electrode material for chemical vapor deposition, sealing the pores of the carbon coating layer to form a carbon layer structure with a complete structure; thus, SiO X / Microcrystalline graphite negative electrode material.

[0074] As a preferred embodiment, in S1, the solvent of the silicon source solution is ethanol.

[0075] Preferably, the pH of the mixed solution is adjusted by ammonia water. The raw materials for the first water bath heating reaction include silicon source, ammonia water and water, and the silicon source and water undergo hydrolysis and condensation reaction under the action of ammonia water to form silicic acid gel.

[0076] Preferably, the heating conditions include a temperature of 40 to 60° C., a reaction time of 1 to 3 hours, and a pH of 9 to 12. The role of ammonia water can not only promote the hydrolysis reaction and assist the nucleation rate of silicon dioxide, but also adjust the pH value of the hydrolysis reaction system.

[0077] Preferably, the ultrasonic condition is an ultrasonic frequency of 20-40 kHz.

[0078] Preferably, the volume ratio of the silicon source to water is 1:1 to 1:2; more preferably, the silicon source is tetraethyl orthosilicate.

[0079] Preferably, the temperature of the first water bath heating is 40-60° C.; the reaction time is 1-3 hours; after the reaction is completed, the silicon source solution is continuously added dropwise until no white precipitate is generated.

[0080] Preferably, the second water bath heating conditions include 60-80° C. and heating for 0.5-1 h.

[0081] As the most preferred embodiment, the temperature of the second water bath heating is higher than the temperature of the first water bath heating.

[0082] More preferably, the difference between the temperature of the second water bath heating and the temperature of the first water bath heating is 20-35°C.

[0083] As a preferred embodiment, in S2, the temperature of the hydrothermal reaction is 180-220° C., and the reaction time is 2-10 h.

[0084] As a preferred implementation, in S3, the drying temperature is 100-120° C., and the drying time is 5-8 hours.

[0085] Preferably, the high temperature calcination conditions include a calcination temperature of 800-1000° C. and a calcination time of 1-3 hours.

[0086] Preferably, in S3 and S4, the inert gas is nitrogen or argon.

[0087] As a preferred embodiment, in S4, the carbon source precursor includes soft carbon or hard carbon.

[0088] Preferably, the carbon source precursor includes at least one of petroleum pitch, coal pitch, mesophase pitch, phenolic resin, epoxy resin, coal tar and heavy oil.

[0089] As a preferred embodiment, in S5, the organic carbon source includes a combination of one or more of methane, ethane, propane, acetylene, ethylene, propylene, and toluene.

[0090] The chemical vapor deposition conditions include: feeding the negative electrode material precursor into a fluidized bed reactor, the reaction pressure is 0.2-0.3 MPa, and the reaction temperature is 700-800°C.

[0091] As a preferred embodiment, the microcrystalline graphite is microcrystalline graphite particles obtained by crushing, flotation, pulverizing, grading and purifying microcrystalline graphite ore.

[0092] As a preferred embodiment, the carbon content of the microcrystalline graphite particles is ≥99.5%, D 50 =8~18μm, tap density is 0.5-1g / cc, specific surface area is 5-15m 2 / g.

[0093] SiO with a core-shell structure prepared by any of the above technical solutions X / Microcrystalline graphite negative electrode material; the core is SiO X / microcrystalline graphite composite material, nano silicon oxide particles are filled in the gaps between the microcrystalline graphite sheets; the outer shell is a carbon coating layer with a complete carbon layer structure; the carbon coating layer wraps the SiO X / Surface of microcrystalline graphite composite material.

[0094] Preferably, the SiO X / The mass percentage of the core in the microcrystalline graphite negative electrode material is 92~97%; the mass percentage of silicon is 10~25%.

[0095] From the principle analysis, the filling of silicon oxide in the present invention mainly includes two steps. One step is hydrolysis and condensation reaction. In this step, after the microcrystalline graphite is dispersed under ultrasonic conditions, the interstices of the microcrystalline graphite grains are enlarged, and ethyl orthosilicate can enter the interstices of the grains, and then nucleate in situ to complete the initial filling; however, the silica nucleus cannot effectively grow during the hydrolysis and condensation reaction process of this step, resulting in insufficient filling of the interstices of the microcrystalline graphite; then gelation is performed through a hydrothermal reaction to achieve secondary filling. The hydrothermal reaction uses excess ethyl orthosilicate, ammonia water, and ethanol to react, generate silica gel in the interstices of the microcrystalline graphite, and at the same time encapsulate the nano-silica nuclei generated by hydrolysis and condensation, and continue to deposit.

[0096] Specifically, ethyl orthosilicate (or tetraethyl silicate or tetraethoxysilane) is selected as the silicon source for in-situ generation of nano-silica on the surface of microcrystalline graphite and in the gaps between grains. The preparation process is based on the sol-gel principle and is achieved through the hydrolysis condensation reaction of ethyl orthosilicate. Ethyl orthosilicate is hydrolyzed in water to form monosilicic acid and alcohol. As the hydrolysis proceeds, the monosilicic acid further undergoes a condensation reaction to form a silicon dioxide network structure. By controlling the pH and reaction temperature, nucleation is rapidly achieved on the surface of the microcrystalline graphite and in the gaps between grains to generate nano-silica particles.

[0097] ‌Gelation‌: In order to further fill the gaps between the microcrystalline graphite, the present invention performs secondary filling by a hydrothermal method, and causes excess ethyl orthosilicate to undergo a gelation reaction. The gel is further filled in the gaps between the grains and wraps the in-situ grown silica nanoparticles to generate a silica precursor.

[0098] ‌ Drying and heat treatment ‌: After drying and heat treatment, the silica precursor is obtained into nano-scale silica particle clusters, and finally into nano-silicon oxide particles through disproportionation reaction. This step not only removes the water and organic matter in the gel, but also further solidifies the silica particles in situ and deposits them on the surface and gaps of microcrystalline graphite. Through the above steps, pure and uniformly distributed nano-SiOx particles can be obtained, with a particle size of 20~60nm.

[0099] The technical solution of the present invention is described in detail below through specific embodiments.

[0100] Example 1

[0101] This embodiment provides a SiO X / A method for preparing a microcrystalline graphite negative electrode material, the specific steps comprising:

[0102] S1. In situ growth: prepare tetraethyl orthosilicate solution (10mL tetraethyl orthosilicate and 50mL anhydrous ethanol), add 20mL distilled water to form a mixed solution; add 2g microcrystalline graphite to disperse in the mixed solution, stir evenly, add 25% mass fraction of ammonia water, adjust pH=9, and heat in a water bath at 60℃ under ultrasonic conditions for the first time to produce a white precipitate, until the precipitate stops increasing; then, increase the temperature to 80℃ and heat in a water bath for the second time to obtain a mixed solution.

[0103] Microcrystalline graphite is obtained by crushing, flotation, pulverization, classification and purification of microcrystalline graphite ore. The carbon content of microcrystalline graphite particles = 99.990%, D 50 =17.4μm, tap density is 0.876g / cc, specific surface area is 6.012m 2 / g.

[0104] S2. Hydrothermal reaction: The mixed solution was added to a reactor and subjected to a hydrothermal reaction at 180°C to obtain SiO X / microcrystalline graphite precursor; the purpose of this step is to perform secondary filling, further allowing the excess silicon source in the hydrolysis reaction to react to generate silica gel, and fill it on the surface of the microcrystalline graphite and in the gaps between the grains, and then undergo hydrolysis reaction and hydrothermal reaction in sequence to obtain a gel precursor.

[0105] S3. Drying and calcining: The SiO X The microcrystalline graphite precursor was dried at 100 °C for 8 h and calcined at 180 °C for 2 h in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite composite material; the SiO X / The precursor of microcrystalline graphite is silica gel. During the calcination process, the precursor in gel form generates silicon dioxide particles. Further, silicon dioxide undergoes a disproportionate reaction to generate silicon oxide, which is finally attached to the surface of microcrystalline graphite in the form of silicon oxide and filled in the gaps between the grains of microcrystalline graphite. At this point, the filling process of microcrystalline graphite is completed, and SiO X / microcrystalline graphite composite materials.

[0106] S4. Coating carbonization: In the SiO X 10% petroleum asphalt is added to the MgO / microcrystalline graphite composite material, the mixture is evenly mixed, and then carbonized in a nitrogen atmosphere at 1150°C to form a carbon coating layer to obtain a negative electrode material precursor.

[0107] S5. Pore sealing: After ultrasonic cleaning and drying, the negative electrode material precursor is sent into a fluidized bed reactor, and the reaction pressure is controlled at 0.2MPa and the reaction temperature is controlled between 700 and 800°C. Acetylene is introduced for decomposition and pore filling deposition to seal the pores of the carbon coating layer and form a carbon coating layer with a complete carbon layer structure; thus, SiO X / Microcrystalline graphite negative electrode material.

[0108] The prepared SiO X / In microcrystalline graphite negative electrode materials, SiO X / The mass percentage of microcrystalline graphite composite material in negative electrode material is 92~97%.

[0109] See also Figure 1 This is a cross-sectional SEM image of the microcrystalline graphite particles used in this embodiment. It can be seen from the image that there are a large number of gaps between the microcrystalline graphite grains.

[0110] See also Figure 2 The prepared SiO X / SEM image of the cross section of microcrystalline graphite negative electrode material. It can be seen from the image that the gaps between the microcrystalline graphite grains in the negative electrode material have been almost completely filled with silicon oxide.

[0111] See also Figure 3 The SiO prepared in this example X / The first charge and discharge curve of microcrystalline graphite negative electrode material. It can be seen from the figure that the first charge capacity is 1191.83mAh / g.

[0112] See also Figure 4 The SiO prepared in this example X / The capacity and capacity retention rate curve of the microcrystalline graphite negative electrode material after 506 cycles. It can be seen from the figure that the material cycle capacity retention rate is 86.41% (of which the 500-cycle capacity retention rate is 86.54%)

[0113] The specific physical and electrochemical performance test results are shown in Table 1.

[0114] Example 2

[0115] This embodiment provides a SiO X / A method for preparing a microcrystalline graphite negative electrode material, comprising:

[0116] S1. In situ growth: prepare tetraethyl orthosilicate solution (10mL tetraethyl orthosilicate and 50mL anhydrous ethanol), add 20mL distilled water to form a mixed solution; add 2g microcrystalline graphite and disperse it in the mixed solution, stir evenly and add ammonia water, adjust the pH to 9, and heat it in a water bath at 50℃ under ultrasonic conditions for the first time until there is no increase of white precipitate; heat it in a water bath at 70℃ for the second time to obtain a mixed solution.

[0117] Microcrystalline graphite is obtained by crushing, flotation, pulverization, classification and purification of microcrystalline graphite ore. The carbon content of microcrystalline graphite particles = 99.678%, D 50 =12.6μm, tap density is 0.721g / cc, specific surface area is 6.889m 2 / g.

[0118] S2. Hydrothermal reaction: The mixed solution was added to a reactor and subjected to a hydrothermal reaction at 180°C to obtain SiO X / microcrystalline graphite precursor; the purpose of this step is to perform secondary filling, further allowing the excess silicon source in the hydrolysis reaction to react to generate silica gel, and fill it on the surface of the microcrystalline graphite and in the gaps between the grains, and then undergo hydrolysis reaction and hydrothermal reaction in sequence to obtain a gel precursor.

[0119] S3. Drying and calcining: The SiO X The microcrystalline graphite precursor was dried at 110 °C for 6 h and calcined at 900 °C for 1 h in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite composite material; the SiO X / The precursor of microcrystalline graphite is silica gel. During the calcination process, the precursor in gel form generates silicon dioxide particles. Further, silicon dioxide undergoes a disproportionate reaction to generate silicon oxide, which is finally attached to the surface of microcrystalline graphite in the form of silicon oxide and filled in the gaps between the grains of microcrystalline graphite. At this point, the filling process of microcrystalline graphite is completed, and SiO X / microcrystalline graphite composite materials.

[0120] S4. Coating carbonization: In the SiO X 15% epoxy resin is added to the MgO / microcrystalline graphite composite material, the mixture is evenly mixed, and then carbonized in a nitrogen atmosphere at 1250°C to form a carbon coating layer to obtain a negative electrode material precursor.

[0121] S5. Pore sealing: The negative electrode material precursor is fed into a fluidized bed reactor, and the reaction pressure is controlled at 0.2 MPa, and the reaction temperature is controlled at 700-800°C. Acetylene is introduced for decomposition and pore filling deposition, and the pores of the carbon coating layer are sealed to form a carbon coating layer with a complete carbon layer structure; thus, SiO X / Microcrystalline graphite negative electrode material.

[0122] The specific physical and electrochemical performance test results are shown in Table 1.

[0123] Example 3

[0124] This embodiment provides a SiO X / A method for preparing a microcrystalline graphite negative electrode material, comprising:

[0125] S1. In-situ growth: Prepare a tetraethyl orthosilicate solution (10 mL tetraethyl orthosilicate and 50 mL anhydrous ethanol), add 20 mL distilled water to form a mixed solution; add 2 g of microcrystalline graphite to disperse in the mixed solution, stir evenly, add ammonia water, adjust pH = 9, and heat in a water bath at 40 ° C for the first time under ultrasonic conditions until there is no increase in white precipitation; heat in a water bath at 70 ° C for the second time to obtain a mixed solution; microcrystalline graphite is microcrystalline graphite particles obtained by crushing, flotation, crushing, grading and purification of microcrystalline graphite ore. The carbon content of microcrystalline graphite particles = 99.890%, D 50 =14.2μm, tap density is 0.806g / cc, specific surface area is 6.553m 2 / g.

[0126] S2. Hydrothermal reaction: The mixed solution was added to a reactor and subjected to a hydrothermal reaction at 180°C to obtain SiO X / microcrystalline graphite precursor; the purpose of this step is to perform secondary filling, further allowing the excess silicon source in the hydrolysis reaction to react to generate silica gel, and fill it on the surface of the microcrystalline graphite and in the gaps between the grains, and then undergo hydrolysis reaction and hydrothermal reaction in sequence to obtain a gel precursor.

[0127] S3. Drying and calcining: The SiO X The microcrystalline graphite precursor was dried at 120 °C for 5 h and calcined at 800 °C for 1 h in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite composite material; the SiO X / The precursor of microcrystalline graphite is silica gel. During the calcination process, the precursor in gel form generates silicon dioxide particles. Further, silicon dioxide undergoes a disproportionate reaction to generate silicon oxide, which is finally attached to the surface of microcrystalline graphite in the form of silicon oxide and filled in the gaps between the grains of microcrystalline graphite. At this point, the filling process of microcrystalline graphite is completed, and SiO X / microcrystalline graphite composite materials.

[0128] S4. Coating carbonization: In the SiO X 6% coal tar pitch was added to the MgO / microcrystalline graphite composite material, the mixture was evenly mixed, and carbonized at 1200°C in a nitrogen atmosphere to form a carbon coating layer to obtain a negative electrode material precursor.

[0129] S5. Pore sealing: The negative electrode material precursor is fed into a fluidized bed reactor, and the reaction pressure is controlled at 0.2 MPa, and the reaction temperature is controlled at 700-800°C. Acetylene is introduced for decomposition and pore filling deposition, and the pores of the carbon coating layer are sealed to form a carbon coating layer with a complete carbon layer structure; thus, SiO X / Microcrystalline graphite negative electrode material.

[0130] The specific physical and electrochemical performance test results are shown in Table 1.

[0131] Example 4

[0132] This embodiment provides a SiO X / A method for preparing a microcrystalline graphite negative electrode material, the specific steps comprising:

[0133] S1. In situ growth: prepare tetraethyl orthosilicate solution (10mL tetraethyl orthosilicate and 50mL anhydrous ethanol), add 20mL distilled water to form a mixed solution; add 2g microcrystalline graphite and disperse it in the mixed solution, stir evenly and add ammonia water, adjust the pH to 9, and heat it in a water bath at 40℃ under ultrasonic conditions for the first time to produce a white precipitate, until the precipitate stops increasing; then, increase the temperature to 60℃ and heat it in a water bath for the second time to obtain a mixed solution.

[0134] Microcrystalline graphite is obtained by crushing, flotation, pulverization, classification and purification of microcrystalline graphite ore. The carbon content of microcrystalline graphite particles = 99.990%, D 50 =17.4μm, tap density is 0.876g / cc, specific surface area is 6.012m 2 / g.

[0135] S2. Hydrothermal reaction: The mixed solution was added to a reactor and subjected to a hydrothermal reaction at 180°C to obtain SiO X / microcrystalline graphite precursor; the purpose of this step is to perform secondary filling, further allowing the excess silicon source in the hydrolysis reaction to react to generate silica gel, and fill it on the surface of the microcrystalline graphite and in the gaps between the grains, and then undergo hydrolysis reaction and hydrothermal reaction in sequence to obtain a gel precursor.

[0136] S3. Drying and calcining: The SiO X The microcrystalline graphite precursor was dried at 100 °C for 8 h and calcined at 180 °C for 2 h in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite composite material; the SiO X / The precursor of microcrystalline graphite is silica gel. During the calcination process, the precursor in gel form generates silicon dioxide particles. Further, silicon dioxide undergoes a disproportionate reaction to generate silicon oxide, which is finally attached to the surface of microcrystalline graphite in the form of silicon oxide and filled in the gaps between the grains of microcrystalline graphite. At this point, the filling process of microcrystalline graphite is completed, and SiO X / microcrystalline graphite composite materials.

[0137] S4. Coating carbonization: In the SiO X 10% petroleum asphalt is added to the MgO / microcrystalline graphite composite material, the mixture is evenly mixed, and then carbonized in a nitrogen atmosphere at 1150°C to form a carbon coating layer to obtain a negative electrode material precursor.

[0138] S5. Pore sealing: The negative electrode material precursor is fed into a fluidized bed reactor, and the reaction pressure is controlled at 0.2 MPa, and the reaction temperature is controlled at 700-800°C. Acetylene is introduced for decomposition and pore filling deposition, and the pores of the carbon coating layer are sealed to form a carbon coating layer with a complete carbon layer structure; thus, SiO X / Microcrystalline graphite negative electrode material.

[0139] The specific physical and electrochemical performance test results are shown in Table 1.

[0140] Example 5

[0141] This embodiment provides a SiO X / A method for preparing a microcrystalline graphite negative electrode material, the specific steps comprising:

[0142] S1. In situ growth: prepare tetraethyl orthosilicate solution (10mL tetraethyl orthosilicate and 50mL anhydrous ethanol), add 20mL distilled water to form a mixed solution; add 2g microcrystalline graphite to disperse in the mixed solution, stir evenly, add 25% mass fraction of ammonia water, adjust pH=9, and heat in a water bath at 60℃ under ultrasonic conditions for the first time to produce a white precipitate, until the precipitate stops increasing; then, increase the temperature to 80℃ and heat in a water bath for the second time to obtain a mixed solution.

[0143] Microcrystalline graphite is obtained by crushing, flotation, pulverization, classification and purification of microcrystalline graphite ore. The carbon content of microcrystalline graphite particles = 99.990%, D 50 =17.4μm, tap density is 0.876g / cc, specific surface area is 6.012m 2 / g.

[0144] S2. Hydrothermal reaction: The mixed solution was added to a reactor and subjected to a hydrothermal reaction at 220°C to obtain SiO X / microcrystalline graphite precursor; the purpose of this step is to perform secondary filling, further allowing the excess silicon source in the hydrolysis reaction to react to generate silica gel, and fill it on the surface of the microcrystalline graphite and in the gaps between the grains, and then undergo hydrolysis reaction and hydrothermal reaction in sequence to obtain a gel precursor.

[0145] S3. Drying and calcining: The SiO X The microcrystalline graphite precursor was dried at 100 °C for 8 h and calcined at 180 °C for 2 h in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite composite material; the SiO X / The precursor of microcrystalline graphite is silica gel. During the calcination process, the precursor in gel form generates silicon dioxide particles. Further, silicon dioxide undergoes a disproportionate reaction to generate silicon oxide, which is finally attached to the surface of microcrystalline graphite in the form of silicon oxide and filled in the gaps between the grains of microcrystalline graphite. At this point, the filling process of microcrystalline graphite is completed, and SiO X / microcrystalline graphite composite materials.

[0146] S4. Coating carbonization: In the SiO X 10% petroleum asphalt is added to the MgO / microcrystalline graphite composite material, the mixture is evenly mixed, and then carbonized in a nitrogen atmosphere at 1150°C to form a carbon coating layer to obtain a negative electrode material precursor.

[0147] S5. Pore sealing: The negative electrode material precursor is fed into a fluidized bed reactor, and the reaction pressure is controlled at 0.2 MPa, and the reaction temperature is controlled at 700-800°C. Acetylene is introduced for decomposition and pore filling deposition, and the pores of the carbon coating layer are sealed to form a carbon coating layer with a complete carbon layer structure; thus, SiO X / Microcrystalline graphite negative electrode material.

[0148] Example 6

[0149] The difference between this embodiment and embodiment 1 is that in the in-situ growth stage in S1, the mass of microcrystalline graphite is 2 g, the volume of tetraethyl orthosilicate is 30 mL, and the other conditions and steps are the same as those in embodiment 1.

[0150] Comparative Example 1

[0151] This embodiment provides a SiO X / A method for preparing a microcrystalline graphite negative electrode material, comprising:

[0152] S1. In-situ growth: Prepare a tetraethyl orthosilicate solution (10mL tetraethyl orthosilicate and 50mL anhydrous ethanol), add 20mL distilled water to form a mixed solution; add 2g of microcrystalline graphite to disperse in the mixed solution, stir evenly, adjust pH to 9 with 25% ammonia water, heat in a water bath at 60℃ for the first time under ultrasonic conditions until white precipitate does not increase; heat in a water bath at 60℃ for the second time to obtain a mixed solution; microcrystalline graphite is microcrystalline graphite particles obtained by crushing, flotation, pulverization, classification and purification of microcrystalline graphite ore. Carbon content of microcrystalline graphite particles = 99.890%, D 50 =14.2μm, tap density is 0.806g / cc, specific surface area is 6.553m 2 / g.

[0153] S2. Hydrothermal reaction: The mixed solution was added to a reactor and subjected to a hydrothermal reaction at 220°C to obtain SiO X / microcrystalline graphite precursor; the purpose of this step is to perform secondary filling, further allowing the excess silicon source in the hydrolysis reaction to react to generate silica gel, and fill it on the surface of the microcrystalline graphite and in the gaps between the grains, and then undergo hydrolysis reaction and hydrothermal reaction in sequence to obtain a gel precursor.

[0154] S3. Drying and calcining: The SiO X The microcrystalline graphite precursor was dried at 120 °C for 5 h and calcined at 800 °C for 1 h in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite composite material; the SiO X / The precursor of microcrystalline graphite is silica gel. During the calcination process, the precursor in gel form generates silicon dioxide particles. Further, silicon dioxide undergoes a disproportionate reaction to generate silicon oxide, which is finally attached to the surface of microcrystalline graphite in the form of silicon oxide and filled in the gaps between the grains of microcrystalline graphite. At this point, the filling process of microcrystalline graphite is completed, and SiO X / microcrystalline graphite composite materials.

[0155] S4. Coating carbonization: In the SiO X 6% coal tar was added to the microcrystalline graphite composite material, mixed evenly, and carbonized at 1200 °C in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite negative electrode material, forming a carbon coating layer to obtain a negative electrode material precursor.

[0156] S5. Pore sealing: The negative electrode material precursor is fed into a fluidized bed reactor, and the reaction pressure is controlled at 0.2 MPa, and the reaction temperature is controlled at 700-800°C. Acetylene is introduced for decomposition and pore filling deposition, and the pores of the carbon coating layer are sealed to form a carbon coating layer with a complete carbon layer structure; thus, SiO X / Microcrystalline graphite negative electrode material.

[0157] Comparative Example 2

[0158] This embodiment provides a SiO X / A method for preparing a microcrystalline graphite negative electrode material, comprising:

[0159] S1. In-situ growth: Prepare a tetraethyl orthosilicate solution (10mL tetraethyl orthosilicate and 50mL anhydrous ethanol), add 20mL distilled water to form a mixed solution; add 2g of microcrystalline graphite to disperse in the mixed solution, stir evenly, add 25% ammonia water to adjust the pH to 9, and heat it in a water bath at 40℃ under ultrasonic conditions for the first time until the white precipitate does not increase; heat it in a water bath at 80℃ for the second time to obtain a mixed solution; microcrystalline graphite is microcrystalline graphite particles obtained by crushing, flotation, crushing, grading and purification of microcrystalline graphite ore. The carbon content of microcrystalline graphite particles = 99.890%, D 50 =14.2μm, tap density is 0.806g / cc, specific surface area is 6.553m 2 / g.

[0160] S2. Hydrothermal reaction: The mixed solution was added to a reactor and subjected to a hydrothermal reaction at 220°C to obtain SiO X / microcrystalline graphite precursor; the purpose of this step is to perform secondary filling, further allowing the excess silicon source in the hydrolysis reaction to react to generate silica gel, and fill it on the surface of the microcrystalline graphite and in the gaps between the grains, and then undergo hydrolysis reaction and hydrothermal reaction in sequence to obtain a gel precursor.

[0161] S3. Drying and calcining: The SiO X The microcrystalline graphite precursor was dried at 120 °C for 5 h and calcined at 800 °C for 1 h in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite composite material; the SiO X / The precursor of microcrystalline graphite is silica gel. During the calcination process, the precursor in gel form generates silicon dioxide particles. Further, silicon dioxide undergoes a disproportionate reaction to generate silicon oxide, which is finally attached to the surface of microcrystalline graphite in the form of silicon oxide and filled in the gaps between the grains of microcrystalline graphite. At this point, the filling process of microcrystalline graphite is completed, and SiO X / microcrystalline graphite composite materials.

[0162] S4. Coating carbonization: In the SiO X 6% coal tar was added to the microcrystalline graphite composite material, mixed evenly, and carbonized at 1200 °C in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite negative electrode material, forming a carbon coating layer to obtain a negative electrode material precursor.

[0163] S5. Pore sealing: The negative electrode material precursor is fed into a fluidized bed reactor, and the reaction pressure is controlled at 0.2 MPa, and the reaction temperature is controlled at 700-800°C. Acetylene is introduced for decomposition and pore filling deposition, and the pores of the carbon coating layer are sealed to form a carbon coating layer with a complete carbon layer structure; thus, SiO X / Microcrystalline graphite negative electrode material.

[0164] Comparative Example 3

[0165] This embodiment provides a SiO X / A method for preparing a microcrystalline graphite negative electrode material, comprising:

[0166] S1. In-situ growth: Prepare a tetraethyl orthosilicate solution (10mL tetraethyl orthosilicate and 50mL anhydrous ethanol), add 20mL distilled water to form a mixed solution; add 2g of microcrystalline graphite to disperse in the mixed solution, stir evenly, adjust pH to 9 with 25% ammonia water, heat in a water bath at 40℃ for the first time under ultrasonic conditions until white precipitate does not increase; heat in a water bath at 50℃ for the second time to obtain a mixed solution; microcrystalline graphite is microcrystalline graphite particles obtained by crushing, flotation, pulverization, classification and purification of microcrystalline graphite ore. Carbon content of microcrystalline graphite particles = 99.890%, D 50 =14.2μm, tap density is 0.806g / cc, specific surface area is 6.553m 2 / g.

[0167] S2. Hydrothermal reaction: The mixed solution was added to a reactor and subjected to a hydrothermal reaction at 220°C to obtain SiO X / microcrystalline graphite precursor; the purpose of this step is to perform secondary filling, further allowing the excess silicon source in the hydrolysis reaction to react to generate silica gel, and fill it on the surface of the microcrystalline graphite and in the gaps between the grains, and then undergo hydrolysis reaction and hydrothermal reaction in sequence to obtain a gel precursor.

[0168] S3. Drying and calcining: The SiO X The microcrystalline graphite precursor was dried at 120 °C for 5 h and calcined at 800 °C for 1 h in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite composite material; the SiO X / The precursor of microcrystalline graphite is silica gel. During the calcination process, the precursor in gel form generates silicon dioxide particles. Further, silicon dioxide undergoes a disproportionate reaction to generate silicon oxide, which is finally attached to the surface of microcrystalline graphite in the form of silicon oxide and filled in the gaps between the grains of microcrystalline graphite. At this point, the filling process of microcrystalline graphite is completed, and SiO X / microcrystalline graphite composite materials.

[0169] S4. Coating carbonization: In the SiOX 6% coal tar was added to the microcrystalline graphite composite material, mixed evenly, and carbonized at 1200 °C in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite negative electrode material, forming a carbon coating layer to obtain a negative electrode material precursor.

[0170] S5. Pore sealing: The negative electrode material precursor is fed into a fluidized bed reactor, and the reaction pressure is controlled at 0.2 MPa, and the reaction temperature is controlled at 700-800°C. Acetylene is introduced for decomposition and pore filling deposition, and the pores of the carbon coating layer are sealed by a gas phase carbon deposition method to form a carbon coating layer with a complete carbon layer structure; thus, SiO X / Microcrystalline graphite negative electrode material.

[0171] Comparative Example 4

[0172] The only difference between this comparative example and Example 1 is that the temperature of the first water bath heating in S1 is 25° C., and the other steps are the same.

[0173] Comparative Example 5

[0174] The only difference between this comparative example and Example 1 is that the temperature of the second water bath heating in S1 is 90° C., and the other steps are the same.

[0175] Comparative Example 6

[0176] The difference between this comparative example and Example 1 is that the water bath heating for in-situ growth is only performed for the first time, which specifically includes:

[0177] S1. In situ growth: prepare tetraethyl orthosilicate solution (10mL tetraethyl orthosilicate and 50mL anhydrous ethanol), add 20mL distilled water to form a mixed solution; add 2g microcrystalline graphite and disperse it in the mixed solution, stir evenly, adjust the pH to 9 with 25% ammonia water, and heat it in a water bath at 40℃ under ultrasonic conditions for the first time to produce a white precipitate, until the precipitate stops increasing.

[0178] Microcrystalline graphite is obtained by crushing, flotation, pulverization, classification and purification of microcrystalline graphite ore. The carbon content of microcrystalline graphite particles = 99.990%, D 50 =17.4µm, tap density is 0.876g / cc, specific surface area is 6.012m 2 / g.

[0179] The other steps are the same as those in Example 1.

[0180] Comparative Example 7

[0181] The difference between this comparative example and Example 1 is that the hydrothermal reaction of S2 is not included for secondary filling, and only S1 is grown in situ, followed by drying and calcining. The specific steps include:

[0182] S1. In situ growth: 5 g of microcrystalline graphite was dispersed in a mixed solution of 10 mL of tetraethyl orthosilicate, 50 mL of anhydrous ethanol and 20 mL of distilled water. After stirring evenly, the pH was adjusted to 9. The solution was heated in a water bath at 60 °C under ultrasonic conditions for the first time to produce a white precipitate until the precipitate stopped increasing. Then, the temperature was raised to 80 °C for a second water bath heating to obtain a gel-like precursor.

[0183] Microcrystalline graphite is obtained by crushing, flotation, pulverization, classification and purification of microcrystalline graphite ore. The carbon content of microcrystalline graphite particles = 99.990%, D 50 =17.4μm, tap density is 0.876g / cc, specific surface area is 6.012m 2 / g.

[0184] S2. Drying and calcining: The SiO X The microcrystalline graphite precursor was dried at 100 °C for 8 h and calcined at 180 °C for 2 h in a nitrogen atmosphere to obtain SiO X / microcrystalline graphite composite material; the SiO X / The precursor of microcrystalline graphite is silica gel. During the calcination process, the precursor in gel form generates silicon dioxide particles. Further, silicon dioxide undergoes a disproportionate reaction to generate silicon oxide, which is finally attached to the surface of microcrystalline graphite in the form of silicon oxide and filled in the gaps between the grains of microcrystalline graphite. At this point, the filling process of microcrystalline graphite is completed, and SiO X / microcrystalline graphite composite materials.

[0185] S3. Coating carbonization: In the SiO X 10% petroleum asphalt is added to the MgO / microcrystalline graphite composite material, the mixture is evenly mixed, and then carbonized in a nitrogen atmosphere at 1150°C to form a carbon coating layer to obtain a negative electrode material precursor.

[0186] S5. Pore sealing: The negative electrode material precursor is fed into a fluidized bed reactor, and the reaction pressure is controlled at 0.2 MPa, and the reaction temperature is controlled at 700-800°C. Acetylene is introduced for decomposition and pore filling deposition, and the pores of the carbon coating layer are sealed to form a carbon coating layer with a complete carbon layer structure; thus, SiO X / Microcrystalline graphite negative electrode material.

[0187] Comparative Example 8

[0188] The difference between this comparative example and Example 1 is that in the in-situ growth stage in S1, the mass of microcrystalline graphite is 2 g, the volume of ethyl silicate is 8 mL, and the other conditions and steps are the same as those in Example 1.

[0189] Comparative Example 9

[0190] The difference between this comparative example and Example 1 is that in the in-situ growth stage in S1, the mass of microcrystalline graphite is 2 g, the volume of ethyl silicate is 32 mL, and the other conditions and steps are the same as those in Example 1.

[0191] Comparative Example 10

[0192] The difference between this comparative example and Example 1 is that the steps of coating carbonization of S4 and pore sealing of S5 are not included, and the other conditions and steps are the same as those of Example 1; that is, the SiO prepared in this comparative example X / microcrystalline graphite composite material is directly used as the negative electrode material.

[0193] Comparative Example 11

[0194] The difference between this comparative example and Example 1 is that the step of hydrolysis reaction of S1 is not included, and the microcrystalline graphite is directly filled by a hydrothermal method. Other conditions and steps are the same as those in Example 1.

[0195] Comparative Example 12

[0196] The difference between this comparative example and Example 1 is that the step of pore sealing of S5 is not included, and other conditions and steps are the same as those of Example 1.

[0197] Comparative Example 13

[0198] The difference between this comparative example and Example 1 is that the microcrystalline graphite is not filled and is directly subjected to carbon coating treatment. The specific steps include:

[0199] In the SiO X 10% petroleum asphalt is added to the MgO / microcrystalline graphite composite material, the mixture is evenly mixed, and then carbonized in a nitrogen atmosphere at 1150°C to form a carbon coating layer to obtain a negative electrode material precursor.

[0200] The negative electrode material precursor is ultrasonically cleaned and dried, and then sent into a fluidized bed reactor. When the reaction pressure is controlled at 0.2 MPa and the reaction temperature is controlled between 700 and 800 °C, acetylene is introduced for decomposition and pore filling deposition, and the pores of the carbon coating layer are sealed to form a carbon coating layer with a complete carbon layer structure. Thus, SiO X / Microcrystalline graphite negative electrode material.

[0201] The material properties of the negative electrode materials prepared in the above embodiments and comparative examples were tested, including specific surface area test, tap density test and true density test. X / microcrystalline graphite negative electrode material was used as the negative electrode to assemble button cells and conduct electrochemical performance tests. The specific test results are shown in Table 1.

[0202] Table 1 Physical properties and electrochemical performance test results of the embodiments and comparative examples

[0203]

[0204] From the experimental results shown in Table 1 above, it can be seen that the in-situ grown SiO x Microcrystalline graphite negative electrode materials have excellent electrochemical properties. The capacity of negative electrode materials is significantly improved, the first effect can be effectively controlled, and SiO x Filled in the microcrystalline graphite matrix, the tap density and true density of the material are improved. Microcrystalline graphite limits the SiO x The volume expansion of SiO x The particles provide a three-dimensional conductive network structure, making SiO x The capacity of the material is effectively utilized, and the volume expansion effect is greatly weakened; therefore, for the technical solution provided by the present invention, the changes in tap density and electrochemical properties can also reflect the SiO x The situation where particles are filled into the gaps in graphite.

[0205] Comparative Examples 1 to 3 respectively studied the effects of the first and second water bath heating temperatures and the temperature difference on the performance of the negative electrode material. In Comparative Example 1, since the two water bath temperatures were the same, SiO x The particles cannot grow and do not grow completely in the gaps between the microcrystalline graphite. The final material has low tap density and true density. x The specific capacity of the material is poor, and the final capacity of the material is low; in Comparative Example 2, due to the large temperature difference between the two water baths, the SiO x The particles grow quickly, and the large particles formed occupy the gaps between the microcrystalline graphite, which cannot provide effective space for the secondary filling of the subsequent hydrothermal reaction, resulting in the final internal SiO x The contact between the material and the graphite particles is poor, the filling effect of the final composite material is not good, the tap density and true density of the material are not significantly improved, the capacity is low, and the large particles of SiO x The volume expansion cannot be effectively controlled, resulting in low initial efficiency and cycle retention rate of the material; in Comparative Example 3, due to the small temperature difference and the low water bath temperature of the second time, SiO x The particles cannot grow and do not grow completely in the gaps between the microcrystalline graphite. The final material has low tap density and true density.x The specific capacity of the material is poor, and the final capacity of the material is low; in Comparative Example 4, due to the low temperature of the first water bath, SiO x The nucleation rate is too slow, SiO x The growth started during the nucleation process and continued during the secondary water bath process. The large particles formed occupied the gaps between the microcrystalline graphite and could not provide effective space for the secondary filling of the subsequent hydrothermal reaction, resulting in the internal SiO x The contact between the material and the graphite particles is poor, the filling effect of the final composite material is not good, the tap density and true density of the material are not significantly improved, the capacity is low, and the large particles of SiO x The volume expansion cannot be effectively controlled, resulting in low initial efficiency and cycle retention rate of the material; in Comparative Example 5, due to the high temperature of the secondary water bath, the primary SiO x The particles grow quickly, and the large particles formed occupy the gaps between the microcrystalline graphite, which cannot provide effective space for the secondary filling of the subsequent hydrothermal reaction, resulting in the final internal SiO x The contact between the material and the graphite particles is poor, the filling effect of the final composite material is not good, the tap density and true density of the material are not significantly improved, the capacity is low, and the large particles of SiO x The volume expansion cannot be effectively controlled, resulting in low initial efficiency and cycle capacity retention of the material; Comparative Example 6 only carried out water bath heating once, resulting in SiO x The particles cannot grow and do not grow completely in the gaps between the microcrystalline graphite. The final material has low tap density and true density. x The specific capacity of the material is poorly exerted, and the final capacity of the material is low.

[0206] Comparative Example 7 did not undergo hydrothermal reaction, but the SiO grown in the water bath process x The particles are not completely filled in the gaps of microcrystalline graphite, and the internal SiO x The contact between the material and the graphite particles is poor, the filling effect of the final composite material is poor, the material's tap density and true density are low, and the capacity is low.

[0207] Comparative Example 8: Since the amount of silicon source added is too low, it is impossible to add SiO x The growth of particles provides sufficient conditions for the SiO2 to fill the gaps in the microcrystalline graphite. x There are fewer particles, and the tap density, true density and capacity are close to the level of microcrystalline graphite.

[0208] In Comparative Example 9, too much silicon source was added, and compared with Example 6, the filling effect and electrochemical performance were not significantly improved. x There is no enhancement effect on the nucleation and growth of particles.

[0209] Comparative Example 10 SiO X / The microcrystalline graphite composite material has not undergone coating carbonization and pore sealing. Compared with Example 1, its structural stability is significantly worse, and its first coulombic efficiency is also significantly lower. The continuous structural fragmentation and increase of side reactions in the material during the cycle ultimately lead to poor material cycle performance.

[0210] Comparative Example 11 does not include the hydrolysis reaction process, SiO x The particles cannot grow completely in the gaps between microcrystalline graphite, resulting in poor filling effect. Microcrystalline graphite has a poor effect on SiO x The particle volume expansion restriction effect is poor, and the material capacity and initial efficiency are low.

[0211] In Comparative Example 12, the pore structure of the coating layer was not sealed, and the larger specific surface area of ​​the material resulted in more side reactions in the electrolyte, and ultimately the first effect and cycle performance were poor.

[0212] Comparative Example 13 provides a negative electrode material prepared by directly coating microcrystalline graphite with carbon. Compared with Comparative Example 1, SiO x Filling can significantly increase the capacity of the negative electrode material.

[0213] In summary, the present invention utilizes the natural structure of microcrystalline graphite to form SiO x Filling to form SiO X / microcrystalline graphite composite materials, using the pore structure of microcrystalline graphite as SiO x The particle volume expansion provides a buffer space, and the carbon coating layer stabilizes the SiO X / The structure of the microcrystalline graphite composite material enables the microcrystalline graphite negative electrode material to form a stable overall structure, thereby further improving the first coulombic efficiency and cycle performance of the negative electrode material.

[0214] The above are only preferred embodiments of the present invention, which do not limit the protection scope of the present invention. For those skilled in the art, the present invention may have various modifications and changes. Within the spirit and principle of the present invention, changes, modifications, replacements, integrations and parameter changes to these embodiments by conventional substitutions or capable of achieving the same functions without departing from the principles and spirit of the present invention all fall within the protection scope of the present invention.

Claims

1. A SiO X / A method for preparing a microcrystalline graphite negative electrode material, comprising: Providing microcrystalline graphite, using the microcrystalline graphite as a matrix material; SiO2 particles and / or silica gel are grown in situ on the surface of microcrystalline graphite through the hydrolysis reaction of silicon source and filled in the gaps between the grains; and then secondary filling is performed through hydrothermal reaction to obtain SiO X / microcrystalline graphite composite material precursor; The SiO X The precursor of the microcrystalline graphite composite material is dried and calcined at high temperature to obtain SiO X / microcrystalline graphite composites; The SiO X After the / microcrystalline graphite composite material is uniformly mixed with the carbon source material and carbonized, the SiO X The surface of the composite material of microcrystalline graphite forms a carbon coating with a complete carbon layer structure, thereby obtaining a SiO X / Microcrystalline graphite negative electrode material; The hydrolysis reaction comprises: heating in a water bath under ultrasonic conditions, so that the product of the hydrolysis reaction grows in situ on the surface of the microcrystalline graphite and fills the gaps in the microcrystalline graphite; The water bath heating includes a first water bath heating and a second water bath heating; The temperature of the second water bath heating is higher than the temperature of the first water bath heating; the temperature difference is 20-35°C; The temperature of the first water bath heating is 40-60°C; the conditions of the second water bath heating include 60-80°C; Based on 1 g of microcrystalline graphite, the added amount of the silicon source is 5 to 15 mL.

2. SiO according to claim 1 X / A method for preparing a microcrystalline graphite negative electrode material, characterized in that: The hydrothermal reaction includes: the excess silicon source continues to react to produce a white precipitate, which is deposited in the gaps of the microcrystalline graphite for secondary filling to obtain the SiO X / microcrystalline graphite composite material precursor.

3. SiO according to claim 2 X / A method for preparing a microcrystalline graphite negative electrode material, characterized in that: The first water bath heating comprises: dispersing microcrystalline graphite in a silicon source solution, stirring evenly and adjusting the pH, heating under ultrasonic conditions to perform a hydrolysis condensation reaction, and generating a white precipitate to nucleate in situ on the surface of the microcrystalline graphite and in the gaps between the grains; The second water bath heating includes: continuing the hydrolysis condensation reaction, and white precipitates are deposited on the surface of the microcrystalline graphite and in the gaps between the grains.

4. SiO according to claim 3 X / A method for preparing a microcrystalline graphite negative electrode material, characterized in that: The reaction time of the first water bath heating is 1 to 3 hours; After the first water bath heating is completed, the silicon source solution is continued to be added dropwise until no white precipitate is generated; The second water bath heating time is 0.5~1h; Wherein, in the reactions of the first water bath heating and the second water bath heating, the silicon source is kept in excess.

5. SiO according to claim 1 X / A method for preparing a microcrystalline graphite negative electrode material, characterized in that: The following steps are involved: S1. Hydrolysis reaction: disperse the microcrystalline graphite in a mixed solution of water and silicon source solution, stir evenly and adjust the pH with ammonia water, heat in a water bath for the first time under ultrasonic conditions until there is no increase in white precipitate; then heat in a water bath for the second time to obtain a reaction mixture; S2. Hydrothermal reaction: Add the reaction mixture into a reactor and perform a hydrothermal reaction to obtain SiO X / microcrystalline graphite precursor; S3. Drying and calcining: After the precursor is dried, it is calcined at high temperature in an inert gas atmosphere to obtain SiO X / microcrystalline graphite composites; S4. Coating carbonization: In the SiO X A carbon source precursor is added to the microcrystalline graphite composite material, mixed evenly, and then carbonized in an inert gas atmosphere to form a carbon coating layer to obtain a negative electrode material precursor; S5. Pore sealing: introducing an organic carbon source into the negative electrode material precursor, and sealing the pores in the carbon coating layer by chemical vapor deposition to form a carbon coating layer with a complete carbon layer structure; thus, SiO X / Microcrystalline graphite negative electrode material.

6. SiO according to claim 5 X / A method for preparing a microcrystalline graphite negative electrode material, characterized in that: In S1, in the silicon source solution, the silicon source is any one of ethyl orthosilicate, tetraethyl silicate or tetraethoxysilane; and the solvent of the silicon source solution is ethanol; In the silicon source solution, the volume ratio of silicon source to ethanol is 2:(5-10); The volume ratio of the silicon source solution to water is 1:(1-2); The mass percentage of ammonia water is 25%; The first water bath heating includes hydrolysis reaction of silicon source and water under the action of ammonia water; the reaction time is 1-3 hours, and the pH is 9-12; the ultrasonic conditions include a frequency of 20-40kHz; And / or, in S2, the temperature of the hydrothermal reaction is 180-220° C., and the reaction time is 2-10 h; And / or, in S3, the drying temperature is 100-120° C., and the drying time is 5-8 hours; The high temperature calcination conditions include a calcination temperature of 800-1000°C and a calcination time of 1-3h; and / or, in S4, the carbon source precursor comprises soft carbon or hard carbon; The carbonization temperature is 1100-1400°C; In S3 and S4, the inert gas is nitrogen or argon; And / or, in S5, the organic carbon source and SiO X / microcrystalline graphite composite material ratio is 0.04~0.2; The organic carbon source includes one or more of methane, ethane, propane, acetylene, ethylene, propylene, and toluene; The chemical vapor deposition conditions include: feeding the negative electrode material precursor into a fluidized bed reactor, the reaction pressure is 0.2-0.3 MPa, and the reaction temperature is 700-800°C.

7. SiO according to any one of claims 1 to 6 X / A method for preparing a microcrystalline graphite negative electrode material, characterized in that: Microcrystalline graphite is microcrystalline graphite particles obtained by crushing, flotation, pulverization, classification and purification of microcrystalline graphite ore; The carbon content of microcrystalline graphite particles is ≥99.5%, D 50 =8~18μm, tap density is 0.5~1g / cc, specific surface area is 5-15m 2 / g.

8. A SiO X / microcrystalline graphite negative electrode material, prepared by the preparation method according to any one of claims 1 to 7; the SiO X / Microcrystalline graphite negative electrode material has a core-shell structure; the core is SiO X / microcrystalline graphite composites, nano-SiO X The particles are filled in the gaps of the microcrystalline graphite sheets; the outer shell is a carbon coating layer with a complete carbon layer structure; The carbon coating layer wraps the SiO X / Surface of microcrystalline graphite composite material.

9. SiO according to claim 8 X / Microcrystalline graphite negative electrode material, characterized in that The SiO X / The mass percentage of the core in the microcrystalline graphite negative electrode material is 92~97%.

10. A lithium ion battery comprising at least the SiO X / Microcrystalline graphite composite negative electrode material.

Citation Information

Patent Citations

  • Silicon oxide / carbon cathode material of lithium ion battery and preparation method of material

    CN103022446A

  • Silica aerogel / micro-expanded graphite composite material and preparation method and application thereof

    CN109950493A

Cited By

  • Ultrahigh-capacity spherical graphite negative electrode material and production method thereof

    CN120933329A